Calculation of structural behavior of indirect NMR spin-spin couplings in the backbone of nucleic acids - Sychrovský, Vladimír; Vokácová, Zuzana; Sponer, Jirí; Spacková, Nad'a; Schneider, Bohdan (The journal of physical chemistry. B, 2006)
Calculated indirect NMR spin-spin coupling constants (J-couplings) between (31)P, (13)C, and (1)H nuclei were related to the backbone torsion angles of nucleic acids (NAs), and it was shown that J-couplings can facilitate accurate and reliable structural interpretation of NMR measurements and help to discriminate between their distinct conformational classes. A proposed stepwise procedure suggests assignment of the J-couplings to torsion angles from the sugar part to the phosphodiester link. Some J-couplings show multidimensional dependence on torsion angles, the most prominent of which is the effect of the sugar pucker. J-couplings were calculated in 16 distinct nucleic acid conformations, two principal double-helical DNAs, B- and A-, the main RNA form, A-RNA, as well as in 13 other RNA conformations. High-level quantum mechanics calculations used a baseless dinucleoside phosphate as a molecular model, and the effect of solvent was included. The predicted J-couplings correlate reliably with available experimental data from the literature.
Keywords: algoritmy; DNA; Dinucleoside Phosphates; Carbon; Nucleic Acid Conformation; Magnetic Resonance Spectroscopy; uhlík; RNA; Algorithms; magnetická rezonanční spektroskopie; dinukleosidfosfáty; konformace nukleové kyseliny; Hydrogen; vodík